BLACK–WHITE MARITAL MATCHING: RACE, ANTHROPOMETRICS, AND SOCIOECONOMICS. (14th November 2016) - Chiappori, Pierre-André; Oreffice, Sonia; Quintana-Domeque, Climent
Abstract: We analyze the interaction of black–white race with physical and socioeconomic characteristics in the US marriage market, using data from the Panel Study of Income Dynamics. We estimate who inter-racially marries whom along anthropometric and socioeconomic characteristics dimensions. The black women who inter-marry are the thinner and more educated in their group; instead, white women are the fatter and less educated; black or white men who inter-marry are poorer and thinner. While women in "mixed" couples find a spouse who is poorer but thinner than if they intra-married, black men match with a white woman who is more educated than if they intra-married, and a white man finds a thinner spouse in a black woman. Our general findings are consistent with the "social status exchange" hypothesis, but the finding that black men who marry white women tend to be poorer than black men who marry black women is not .